DEVELOPMENT OF A GUIDANCE ACTIVITY SET TO PROMOTE SPIRITUAL WELL-BEING AMONG VOLUNTEER MONKS AT LENG NOEI YI TEMPLE, BANGKOK - Sroichomphu, PhraKasemsak; Woramongkhalo, PhrakhrupaladMarut; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) develop a guidance activity set designed to promote the spiritual well-being of volunteer monks at Wat Leng Neiy Yi, Bangkok, and 2) to examine the effects of using this guidance activity set to promote the spiritual well-being of volunteer monks at Wat Leng Neiy Yi, Bangkok. This study employed a quasi-experimental design. The sample, selected through purposive sampling, consisted of 30 volunteer monks at Wat Leng Noei Yi. The research instruments included: 1) a questionnaire and 2) a set of guidance activities to promote spiritual well-being. Data were analyzed using mean, standard deviation, and statistical testing. The research findings were as follows: 1) The guidance activity set to promote the spiritual well-being of volunteer monks at Wat Leng Neiy Yi, Bangkok, enabled them to become more aware of their role as volunteer monks. The researcher observed that during participation in the activities, all volunteer monks demonstrated increased self-esteem, a greater awareness of their importance in helping society, and expressed appreciation to others. The results showed that: 1) The guidance program resulted in a higher level of spiritual well-being for all participating monk volunteers compared to before the guidance program; and 2) A comparison of the levels of spiritual well-being of the monk volunteers at Wat Leng Neiy Yi before and after the guidance program revealed a statistically significant difference (p < .05) in both individual aspects and overall well-being.